Hybridization kinetics between immobilized double-stranded DNA probes and targets containing embedded recognition segments - Baker, Bryan A. (Oxford University Press, 2011)
We have investigated the time-dependent strand displacement activity of several targets with double-stranded DNA probes (dsProbes) of varying affinity. Here, the relative affinity of various dsProbes is altered through choices in hybridization length (11–15 bases) and the selective inclusion of center mismatches in the duplexes. While the dsProbes are immobilized on microspheres, the soluble, 15 base-long complementary sequence is presented either alone as a short target strand or as a recognition segment embedded within a longer target strand. Compared to the short target, strand displacement activity of the longer targets is slower, but still successful. Additionally, the longer targets exhibit modest differences in the observed displacement rates, depending on the location of recognition segment within the long target. Overall, our study demonstrates that the kinetics of strand displacement activity can be tuned through dsProbe sequence design parameters and is only modestly affected by the location of the complementary segment within a longer target strand.